EFEKTIVITAS LIDAH BUAYA DAN AIR LERI (AIR CUCIAN BERAS) DALAM MENURUNKAN KADAR FORMALIN PADA TAHU - hidayah, nurul; Irianto, Redi Yudha (VISIKES, 2023)
Formalin in food causes long-term health effects. Aloe vera contains saponin compounds and leri water contains proteins that can bind formalin. The purpose of this study was to determine the effectiveness of aloe vera and leri water on reducing formalin levels in tofu. The experimental research design used a factorial Completely Randomized Design (CRD). The treatment in this study was the use of a solution of aloe vera and leri water using a concentration of 100%:0, 80%: 20% , 60%:40, 0:100%, 20%:80% and 40%:60%. The highest mean reduction in formalin levels was using a solution of aloe vera and leri water with a concentration of 0%:100%, namely 76.9 ppm (71.8%), the average decrease in formalin levels in tofu was the lowest using a solution of aloe vera and leri water with a concentration of 100% :0%, namely 15.8 ppm (14.7%). The Kruskal Walls test obtained a significance value of p = 0.006, which means that there are differences in the use of aloe vera solution and leri water in various concentrations for reducing formalin levels in tofu. Keywords: aloe vera, leri water, formalin, tofu.